Curadoria em arte/arqueologia: processos de proto e pós-escavação - Pedro da Silva; Inês Moreira (Midas: Museus e Estudos Interdisciplinares)
The transdisciplinary practice of art/archaeology has been creating a new relationship between the worlds of archaeology and contemporary art. Created a new confluence, where archaeologists and/or artists leverage their research, creative and performative work, we argue that curating in art/archaeology will serve to expand new directions in the field of knowledge production. In this article, we analyse the international literature on this emerging topic, serving as a basis and method for discussing case studies. These case studies refer to examples of Portuguese contemporary artistic creation, namely from the collective Pedra no Rim and the artist João Gomes Gago. From the hypotheses raised by the literature on art/archaeology and its discussion through the selected case studies we highlight how ceramic materiality can serve as a curatorial case study to question the very definition of “archaeological artefact”. From the proposed processes (or methodologies) of proto-excavation and post-excavation, we (re)interpret these artefactual records, from new contemporary artistic formats, of mediation and resignification of a past that will be archaeological. We conclude that art/archaeological curatorship may have a fundamental role in questioning the very definition of “archaeological artefact” as a passive and immutable object or “thing”. That is, art/archaeological curatorship emphasizes the importance of individual perspectives and social and historical relations in the construction of the meaning of archaeological artifacts.